URGENSI FIQIH PARENTING TERHADAP MORALITAS ANAK DIGITAL NATIVE PERSPEKTIF USTADZ ADI HID AYATMELALUI KONTEN YOUTUBE - Milla Ardiah Izzati, Milla; Muliatul Maghfiroh (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the urgency of fiqh parenting in shaping the moral development of digital native children from the perspective of Ustadz Adi Hidayat as conveyed through YouTube content. The research employs a qualitative approach using content analysis as the primary method. Data were collected through non-participant observation, video documentation, and a review of relevant literature. The data were analyzed systematically and objectively to explore the meanings of fiqh parenting values presented in the content, with data validity strengthened through theoretical triangulation and persistent observation. The findings indicate that fiqh parenting as taught by Ustadz Adi Hidayat emphasizes parental role modeling, gentle communication, affection, and the reinforcement of faith-based values as the foundation of children’s moral development. This approach is considered relevant in addressing moral challenges faced by digital native children, such as exposure to negative online content, weakened emotional regulation, and reduced social interaction. Fiqh parenting provides a practical framework for parents to guide children in using digital technology wisely without neglecting spiritual and moral values. This study recommends that future research employ empirical approaches to examine the effectiveness of fiqh parenting implementation in family life and develop adaptive, context-sensitive digital-based parenting education programs.